(untitled) (Andamios, Revista de Investigación Social, 2007)
Among the topics covered by discussion on causation between events is causation that involves omissions. If, by having taken precautions, the robbery would not have occurred, then the omission of not having taken precautions is the cause for the robbery. On the other hand, if the robbery did not take place because of the precautions taken, we say that those precautions are a preventor of the robbery. Some kind of mirror relationship has been suggested from which derives that not taking precautions and removing them is equivalent. In this paper, such an equivalence is analyzed and it is shown that it has no support for the cases which involve states of affairs. Analyzing causation involves dealing with causation by omission and causation of omission. In the first case, omission to take precautions is the cause of a certain disaster. In the second, having taken such precautions is the cause for not obtaining the mentioned disaster: to take precautions is a preventor of the disaster. It has been pointed out that there exists a mirror relationship between omissions and preventors, giving as a consequence that omitting to establish preventors should be equivalent to removing preventors previously provided. In this paper we analyze this equivalence, and conclude that it cannot be supported when states of affairs take place in the role of causes or of effects.